Pemanfaatan Limbah Belimbing Wuluh, Kulit Jeruk, dan Bayam sebagai Sumber Asam Organik: Studi Konsentrasi Asam dan Potensi sebagai Agen Reduktor - Nurrohmah Dwi Mahesti; Hery Muhamad Ansory (Jurnal Farmasi Indonesia, 2024)
Fruit and vegetable waste contains organic acids that can still be utilized, offering new potential as reducing agents in environmentally friendly chemical applications. The samples used in this study include Averrhoa bilimbi, orange peel, and spinach waste, known to contain organic acids. This study aims to optimize the extraction process of organic acids from these samples and identify their potential as reducing agents. The method involves drying and dissolving the waste samples, which were dried at 60°C and then disbanded in aquabidest with varying times and temperatures. The concentration of organic acids was analyzed using alkalimetry and permanganometry to measure total acids and reduce acids. The results show that variations in dissolution time and temperature influence the concentration of dissolved organic acids in the waste samples. The highest concentration was achieved at a dissolution time of 90 minutes and a temperature of 60°C, with concentrations decreasing at longer times and higher temperatures. Qualitative identification indicates that Averrhoa bilimbi and spinach contain oxalic and ascorbic acids, while orange peel contains citric and ascorbic acids. These findings highlight the potential of these samples as reducing agents, especially under optimal dissolution conditions.